Granulomatous mastitis and other inflammatory mastitis simulating breast neoplasms – A retrospective study in the fine needle aspiration cytology clinic of a tertiary care center in eastern India - Pamela Nayak; Meghadipa Mandal; Srishtidhar Mangal (Asian Journal of Medical Sciences, 2024)
Background: Fine needle aspiration cytology (FNAC) is an important diagnostic modality in palpable breast lesions. This together with imaging modality is important in distinguishing benign from malignant lesions of the breast. Granulomatous/inflammatory mastitis forms a small subset of breast lesions that may present as a breast lump. Clinical and radiological features in these cases may mimic malignant breast pathology. Aims and Objectives: The aim of this study was to study the frequency of granulomatous mastitis and other inflammatory mastitis with respect to other neoplastic lesions of the breast, presented in FNAC clinics and to correlate the cytological findings with the clinical presentation of granulomatous and other inflammatory mastitis. Materials and Methods: A retrospective study was conducted in the Department of Pathology in a tertiary care center in Eastern India for duration of 4 years 5 months. Details of all patients who underwent FNAC for breast lesions during the study period were recorded in terms of their clinical presentation, cytological findings, imaging, and ancillary investigations. The findings were then tabulated in a master sheet and analysis done by descriptive statistics using SPSS 25. Results: A total of 154 cases were included with 5 cases (3.2%) of granulomatous and 12 cases (7.8%) of inflammatory mastitis. Age range for granulomatous/inflammatory mastitis was 20–70 years. Lump and pain were the most common complaints followed by inflammatory skin changes and nipple discharge. Very few cases also showed nipple retractions and very occasional systemic symptoms like fever. History of lactation was seen among five cases. Three cases showed positive acid-fast bacilli in Ziehl–Neelsen stain. Radiology was discordant with cytological findings in three cases, where the former suggested a breast neoplastic process. Conclusion: Granulomatous/inflammatory mastitis is a rarely diagnosed entity in breast cytopathology with no standard guidelines for management. Antibiotics antitubercular therapy and corticosteroids are some proposed lines of medical management. In treatment-resistant cases, wide local excision may be done depending on available resources and surveillance opportunities.